ANALISIS KEBIJAKAN PENDIDIKAN RANAH IDENTIFIKASI MASALAH FORMULASI KEBIJAKAN IMPLEMENTASI KEBIJAKAN EVALUASI DAMPAK - Abdul Qohhar Muhyi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Education policy is a crucial part of the national education system because it determines the direction, goals, and strategies for educational implementation. Education policy analysis is a systematic process for reviewing, assessing, and understanding education policy from various perspectives, such as social, political, economic, and cultural perspectives. This study aims to outline the basic concepts of education policy analysis, including the definition, basic principles, and approaches frequently used in analyzing education policy. The method used in this paper is library research with a descriptive qualitative approach. The results of the study indicate that education policy analysis focuses not only on policy content but also on the context of policy formation, the actors involved, the implementation process, and the evaluation of its impact on the ground. Various approaches to policy analysis, such as rational, political, technocratic, and critical approaches, provide a broader understanding of the realities of education policy. Understanding these basic concepts is essential for students, academics, and decision-makers to formulate and implement relevant policies that support improving the quality of education.